DOES TAX PLANNING AFFECT FIRM VALUE OF EUROPEAN COMPANIES? - Daniel Peterson Silaban (Faculty of Economics and Business Universitas Pelita Harapan, 2023)
The purpose of this research is to examine whether firms’ tax planning behavior affect firm value in European companies. In this research, tax planning is measured using Cash Effective Tax Rate (CETR) and Book Tax Difference (BTD) on company value, which is measured using Price-Earnings Ratio. The purpose of doing tax planning is to streamline corporate tax expenditures following applicable regulations. Thus, the existence of corporate tax planning enables the management to estimate firm’s tax expenses. The control variables used in this study are Size and Leverage. The samples used in this study a sample of 10 finance service-related firms listed in the Euronext 100 index for the period from 2018 to 2022. This study uses the EViews 10 test tool and uses a multiple regression test. Results found that BTD has significant impact toward Firm Value, with negative relationship, where CETR has no impact towards Firm Value.